Prevalence of Anxiety Symptoms and Associated Clinical and Sociodemographic Factors in Mexican Adults Seeking Psychological Support for Grief During the COVID-19 Pandemic: A Cross-Sectional Study - Dominguez-Rodriguez, Alejandro; Herdoiza-Arroyo, Paulina Erika; Martínez Arriaga, Reyna Jazmin; Bautista Valerio, Eduardo; Mateu Mollá, Joaquín; de la Rosa-Gómez, Anabel; Farfallini, Luis; Hernández Jiménez, María Jesús; Esquivel Santoveña, Esteban Eugenio; Ramírez-Martínez, Flor Rocío; Castellanos Vargas, Rosa Olimpia; Arzola-Sánchez, Carlos Armando; et al. (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic is one of the greatest challenges in modern history, with more than four million confirmed deaths worldwide. To date, evidence regarding the psychological impact of the COVID-19 pandemic on grievers is scarce for developing countries such as Mexico. This study aimed to assess the levels of anxiety and associated concerns in a sample of Mexican adults bereaved during the COVID-19 outbreak. A cross-sectional study was conducted through the Duelo COVID (COVID Grief) platform, which is a self-guided online treatment. A total of 5,224 participants reported their anxiety, depression, sleep quality, avoidance, and arousal, prolonged grief symptoms, and medication consumption. Independent sample Mann-Whitney U-tests, chi-square tests, and Kruskal-Wallis tests, as well as multinomial logistic regression, were conducted. Results indicated that 90.4% of the participants reported clinical levels of anxiety, depression, and sleep affectations. The people who lost someone during the last 5 months scored higher in normal grief symptoms compared to the people whose loss was 6 months ago or more, and 9.8% of individuals reported the use of prescription medication, with anxiolytics and antidepressants being the most common. Females, younger respondents, unemployed people with a lower educational level, and participants who disclosed a recent suicide attempt were among those who reported medication consumption. Sleep problems were more frequent in older participants.